An electromyographic study of the flexor muscles of the elbow articulation, in weightlifting trained subjects - Gushi, M. S.; Bankoff, A. D. P.; Fonseca Neto, D. R.; Gassi, E. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction Using the resources of electromyography, the present work aims at making clear which muscles are involved in the possible ways of performing flexion exercises of the forearm, either in supination or pronation positions. Methods Ten male right-handed subjects, with at least one-year experience in weightlifting exercises, without previous neuromuscular diseases, aged between 21 and 26 years, were studied in the "Larry Scott" bench, in supination and pronation positions. After taking the "Maximum Load" (M.L.) test, or a maximum repetition, we got the needed percent pattern to establish the loads used in the tests, which was 80% of the M.L. We also got electromyographic records using, a six-channel electromyograph (Lynx) and the AqDados software in four different moments for each subject: an isometric phase lasting five seconds in supination (1), keeping a 90 degrees angle between the arm and forearm; another one in isometric pronation (2); ten repetitions lasting fifty seconds in supination (3); and ten repetitions in pronation (4). Results Firstly, the gross values were normalized, that is to say, the muscular activation, in RMS (Roots Mean Square), of the phase in which 10 repetitions using 80% of the M.L., was adjusted by activating a maximum isometric contraction. This way the percent values of the activations in each moment were evaluated. The T-Test for dependent samples was used so that the evaluation of these values was done. The results of the normalization have shown a similar activation level in the muscles that were involved in the same moment, either in supination or in pronation positions. Using the ANOVA variance analysis, with p<0,05, we conclude that there was no significant difference during the action of those muscles. This way, we can find a joint action of all the flexor muscles of the elbow to endure the load used during the effort as shown on Table1.